2009
DOI: 10.2320/matertrans.mra2008375
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Different Preservative Methods on Fracture Behavior of Bovine Cortical Bone

Abstract: Bone specimens used for evaluating the mechanical properties of bone may not have been necessarily preserved by the same method before they become available. To this end, the mechanical properties of bone may be affected by freezing, a common preservation method, as well as by formalin and other preservation solutions. In this study, bone specimens were preserved by different methods (i.e., freezing, preservation in saline, preservation in ethanol, and preservation in formalin) to examine the effects of each p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
1
6
0
Order By: Relevance
“…6. The trend of the control group corresponds well with the microcrack initiation behavior discussed in a previous report, 4) where a microcrack was assumed to start forming at a displacement w of approximately 0.2 mm, where a remarkable increase in the strain was observed. The relationship between " x and w was assumed to be a downward convex curve with increasing w, showing an exponential increase in the strain particularly in the control group.…”
Section: Resultssupporting
confidence: 55%
“…6. The trend of the control group corresponds well with the microcrack initiation behavior discussed in a previous report, 4) where a microcrack was assumed to start forming at a displacement w of approximately 0.2 mm, where a remarkable increase in the strain was observed. The relationship between " x and w was assumed to be a downward convex curve with increasing w, showing an exponential increase in the strain particularly in the control group.…”
Section: Resultssupporting
confidence: 55%
“…In an effort to quantify the crack growth and fracture in bone, either indentation fracture experiments were used to measure fracture toughness or relate crack propagation with fracture toughness. [9][10][11][12][13] Online loading stages found in literature have rather small dimensions, and thus only limited loads can be applied. 14,15 For the investigation of high strength materials, such as metallic foams or cortical bone, such set-ups become inappropriate.…”
Section: Introductionmentioning
confidence: 99%
“…31 Numerous experimental studies determined the effect of several parameters, that is, sugar, age, hydration, mineralization, preservative method, fatigue loading, strain rate, porosity, anisotropy, demineralization, deproteinization, type of specimen, indentation, shear deformation, bone composition, etc., on fracture parameters of cortical bone. 2123,3264 Many researchers have validated their numerically predicted results with the experimental analysis as well. 22,40,42,47,51,62…”
Section: Experimental and Numerical Analysis Of Cortical Bone Fractur...mentioning
confidence: 91%
“…They concluded that damage around the fracture surface was more in saline stored bovine bone than alcohol stored bone. 45 Some researchers include studied the effect of temperature on the K C of compact bone. 124,125 Yan et al 124 prepared Single-edge V-notched (SEVN) specimens to measure the K C of the bovine cortical bone and manatee rib in the water at 0°C, 10°C, 23°C, 37°C, and 50°C.…”
Section: Experimental and Numerical Analysis Of Cortical Bone Fracture Parametersmentioning
confidence: 99%
See 1 more Smart Citation